ACTIVITY OF SITOTOKSIK ETANOL EXTRACT PLANT GROWTH (Cynometra ramiflora Linn) ON HEAVY CELL, T47D and WiDR - Haryoto Haryoto; Muhtadi Muhtadi; Peni Indrayudha; Tanti Azizah; Andi Suhendi (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2013)
Cynometra ramifolia Linn is known as Sala plant. This plant, especially in Solo City categorized as rare plant and traditionaly used to cure uric acid, diabetes, hypertension, and others pain. It is interesting to know the other activities by done the test for human cancer cell-lines. This research objective to identify the cytotoxicity effects of ethanol extract from C.ramiflora the stem bark and leaves against T47D, HeLa and WiDr cancer cell lines. The cytotoxicity test of ethanol extract from C.ramiflora the stem bark and leaves determined by MTT assay by calculating the level of IC50 which was based on the percentage of the cell death following the 24 hours incubation with the extract. The results showed that ethanol extract of stem bark has cytotoxic effect to HeLa, T47D and WiDr cell-lines with the IC50 of 1000; 0,90 and 6,29 g/mL respectively. The leave cytotoxic effect to HeLa, T47D and WiDr cell-lines with the IC50 of 1,92; 6,37 and 0,41 g/mL respectively. This research indicated that the ethanol extract isolated from C. Ramiflora leaves a selective cytotoxicity effect to WiDr cell line.